Geological aspect analysis for micro hydro power plant site selection based on remote sensing data - Yugo Kumoro; Yuliana Susilowati; Pudji Irasari; Wawan Hendriawan Nur; Yunarto Yunarto (Institute of Advanced Engineering and Science, 2022)
Geological characters analysis is essential for micro hydropower plant (MHP) development planning. This paper presents an analysis of the geological aspect to determine the layout of MHP components based on remote sensing data as part of a solution to addressing power shortages in Sungai Are District, South Ogan Komering Ulu Regency, South Sumatra Province. Remote sensing and topographic map were extracted to identify the potential site. The topographic map and geological analysis were used to calculate the potential of electrical energy and the geological hazard risk, particularly floods and landslides. The results of the study identified four potential sites. Site 1 (Luas River, Ulu Danau Village) and site 3 (Putih River, Gintung Village) are suitable for MHP with a low cost of construction. Site 2 (Pecah Pinggan Village) and site 4 (Simpang Luas Village) are prone to flooding and landslides that makes it suitable for MHP but with a high cost of construction. Based on the geological aspect analysis, it is possible to optimize the hydropower capacity, by adding the volume of water flow from several nearby tributaries channeled into the hydropower flow system through civil construction engineering or by making a cascade design on the tailrace water flow.